A SPECTROPHOTOMETRIC STUDY OF NEODYMIUM(III) COMPLEXATION IN SULFATE SOLUTIONS AT ELEVATED TEMPERATURES - Migdisov A.; Williams-Jones A.E.; Reukov V.V. (My University, 2006)
The formation constants of neodymium complexes in sulfate solutions have been determined spectrophotometrically at temperatures of 30-250 °C and a pressure of 100 bars. The dominant species in the solution are NdSO4+ and Nd(SO4)2-, with the latter complex being more important at higher temperature. Equilibrium constants were calculated for the following reactions: Nd3+ + SO42- = NdSO4+, β1; Nd3+ + 2 · SO42- = Nd(SO4)2-, β2; NdSO4+ + SO42- = Nd(SO4)2-, Ks. The values of β1 and β2, were determined for 30 and 100 °C, whereas for higher temperatures it was only possible to determine the stepwise formation constant Ks. The values of the formation constants obtained in this study for 30 and 100 °C are in excellent agreement with those predicted theoretically by Wood [Wood, S.A., 1990b. The aqueous geochemistry of the rare-earth elements and yttrium. 2. Theoretical predictions of speciation in hydrothermal solutions to 350 °C at saturation water vapor pressure. Chem. Geol. 88 (1-2), 99-125] and Haas et al. [Haas, J.R., Shock, E.L., Sassani, D.C., 1995. Rare earth elements in hydrothermal sysytems: estimates of standard partial molal thermodynamic properties of aqueous complexes of the rare earth elements at high pressures and temperatures. Geochim. Cosmochim. Acta 59 (21), 4329-4350], and those for the stepwise formation constant (Ks) agree reasonably well with the predictions of Wood (1990b). © 2005 Elsevier Inc. All rights reserved.